PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM KERJA TERHADAP KOMPETENSI GURU SMA NEGERI SE KOTA SINTANG - Sumitro, Sumitro; Chiar, H.M; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to obtain data and information about the principal?s leadership and work climate to do with the competency of teachers. This study uses a quantitative approach to the descriptive format of the survey. The study population consists of 92 people who are teachers, civil servants, minimal education DIV or S1 with a minimum of three years teaching experience drawn from four State High Schools in Sintang Regency. The population will then be sampled 75 respondents who later conclusions of this study will apply to the population. This study used a questionnaire as data collection techniques. Furthermore, based on the data analysis result in (1) 84.36% the principal?s leadership of all State High Schools in Sintang Regency included in the category of effective to very effective. (2) 83.58% the work climate of all State High Schools in Sintang Regency are included in the category is conducive to very favorable. (3) 83.10% the teacher?s competency of all State High Schools in Sintang Regency included in the category of good to very good. Keywords: Leadership, Work Climate, Teacher?s Competency